Assessing Mathematics Teachers' Perspectives of Gifted and Talented Education in Saudi Arabian - AlAli , Rommel (Al-Qanṭara, 2025)
The importance of gifted education is being acknowledged worldwide for its impact, on economic growth and Saudi Arabia is no different in valuing this field of education highly. In this research study of a nature the focus is on how mathematics teachers perspective their effectiveness in teaching gifted students in standard classrooms, across Saudi Arabia. A survey was conducted using a 5-point Likert scale consisting of 20 items. Was completed by 130 math teachers who are actively engaged in gifted education. This research centers, on two areas of interest regarding teachers efficacy and abilities to support students and their views on the success of existing programs for gifted education. The results show that teachers generally have views on their competence in teaching students and express confidence in their understanding of the needs of these learners and, in using suitable teaching methods. However, teachers expressed critical views regarding the effectiveness of existing gifted programs. Significant variations in perspectives were observed based on teachers' educational levels, with those holding master's degrees showing perspective that is more positive. Regression analyses further confirmed a notable correlation between higher educational attainment among teachers and positive perspectives of gifted education. The study concludes with recommendations for enhanced professional development opportunities, curriculum adaptation, and policy support to improve the educational outcomes of gifted students in Saudi Arabia.